2017
DOI: 10.1093/ofid/ofx162.075
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Outcomes of Adults with Enterobacteriaceae Bacteremia Receiving Short-Course vs Prolonged-Course Antibiotic Therapy

Abstract: BackgroundThe recommended duration of antibiotic treatment for Enterobacteriaceae bacteremia is between 7 and 14 days. We compared the clinical outcomes of patients receiving short-course (6–10 days) vs prolonged-course (11–15 days) antibiotic therapy for Enterobacteriaceae bacteremia.MethodsA retrospective cohort study was conducted at The Johns Hopkins Hospital, The University of Maryland Medical Center, and The Hospital of the University of Pennsylvania including patients with monomicrobial Enterobacteriace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…In‐hospital mortality occurred in 9 (9%) and 3 (3%) patients in the IVPB and IVP groups, respectively. This is lower but comparable to the 9.8% mortality rate identified by Chotiprasitsakul and colleagues in a study of patients with Enterobacteriaceae bacteremia of a primarily urinary or intra‐abdominal source and similar baseline characteristics to ours 14 . We hypothesize the time of infusion between IVP over 5 min and IVPB over 30 min did not lead to differences in clinical response given the low MICs of our organisms to FEP and MEM, the previously described lack of pharmacokinetic differences in time above MIC between these two forms of administration, and the more favourable outcomes in patients with a low inoculum urinary or intra‐abdominal source of Enterobacteriaceae bacteremia 1,14 …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In‐hospital mortality occurred in 9 (9%) and 3 (3%) patients in the IVPB and IVP groups, respectively. This is lower but comparable to the 9.8% mortality rate identified by Chotiprasitsakul and colleagues in a study of patients with Enterobacteriaceae bacteremia of a primarily urinary or intra‐abdominal source and similar baseline characteristics to ours 14 . We hypothesize the time of infusion between IVP over 5 min and IVPB over 30 min did not lead to differences in clinical response given the low MICs of our organisms to FEP and MEM, the previously described lack of pharmacokinetic differences in time above MIC between these two forms of administration, and the more favourable outcomes in patients with a low inoculum urinary or intra‐abdominal source of Enterobacteriaceae bacteremia 1,14 …”
Section: Discussionsupporting
confidence: 90%
“…More specifically, our population included a limited number of patients with either deep seated infections such as meningitis, osteomyelitis and endocarditis or biofilm‐forming organisms such as P aeruginosa , all of which may be more difficult to eradicate and treat. Although our primary endpoint of escalation of therapy is not consistent with those used in other Gram‐negative bacteremia studies, this endpoint was chosen to minimize confounders in the assessment of IVPB versus IVP forms of administration 14 . Furthermore, close to half of the patients received at least 1 dose of another susceptible antibiotic prior to receiving the study drug, potentially influencing the ability to evaluate microbiological clearance between IVP and IVPB in a population of patients with a urinary source of bacteremia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients with bacterial bloodstream infections still receive between 10 and 14 days of antibiotics, although these durations are based largely on expert opinion, and recent evidence from retrospective analyses and a randomized trial indicate clinical noninferiority between 7-day and 14-day courses. 4,5 Fixed antibiotic durations provide straightforward guidance but do not take into account host characteristics or treatment response. Given high diversity among pathogens and their hosts, another approach would be to individualize durations via biomarker-assisted guidance.…”
mentioning
confidence: 99%
“…(102) Subsequent to this meta-analysis several randomized controlled trials of 7-8 versus 14-15 days of antibiotics in patients with Gram-negative bacteremia (of which the majority had a urinary tract source) found that the shorter course was non-inferior to longer courses in clinical outcome. (80,103,104) A more recent meta-analysis comparing ≤ 10 days to> 10 days of therapy in patients with bacteremia showed no differences in clinical or microbiologic cure nor mortality, however there were only 4 studies available to assess specifically this duration. (105) In an observational study, when source control had been achieved, investigators found that patients with Pseudomonas bacteremia receiving a median of 9 days of therapy (IQR 8-10) had a similar odds of recurrent infection and death as patients who received a median of 16 days (IQR, [14][15][16][17].…”
Section: Adultsmentioning
confidence: 99%